Pengaruh Penambahan Labu Kuning dan Kacang Hijau Ditinjau Dari Sifat Fisik, Organoleptik dan Kandungan Gizi Makanan Tradisional Nagasari - Desi Nur Yuniyanti; Elza Ismail; Joko Susilo (POLTEKKES KEMENKES YOGYAKARTA, 2017)
An effort done to decrease dependence toward rice flour is by changing rice flour with pumpkin. High potentcy of pumpkin andmung beans production in Indonesia is not matched with the public interest on its utilization. Nagasari is a white-coloredtraditional cake with chewy texture and is filled with banana.The addition of yellow pumpkin and mung beans can provideadditional nutrients and as an alternative healthy snack. The research was aimed to know the effect of pumpkin and mungbeans addition on nagasari reviewed from physical properties, organoleptic and nutrient content of nagasari. This researchwas a quasi experimental with simple random sampling. The data of physical properties was analized descriptively. Data offavorite level test was analyzed using Kruskal-Wallis test and if there were differences, it would be continued by Mann-Whitney test. The physical properties of Nagasari with pumpkin addition made the yellow colour looks brighter, its aromawould be decreased and the pumpkin aroma would be stronger, the sweet taste of it will be dominant and the chewy texturecould be decreased. The favorite level of nagasari with variation of pumpkin and mung beans based on the quality of colour,aroma, taste, and texture was significantly different (p<0,05). The addition of pumpkin in nagasari showed the difference ofbetakaroten, so that the more pumpkin added the more betakaroten content. The addition of mung beans in nagasari showedthe difference. Nagasari with mung beans showed the protein content was higher than the one without mungbeans addition.The content of energy, carbohydrate, and fat were not matched with the theory. It might be caused by biased of the researchwhich did not take nagasari sampling homogeneously. Conclusion: There was an effect of pumpkin and mung bean sadditiontoward the physical properties, organoleptic and the nutrient content of the nagasari traditional food.